The Specificity of International Trade Arbitration Within the WTO and the Extent to which Developing Countries are led by it - a Study in the Provisions of the Memorandum of Understanding on Dispute Settlement - Bendriss, Halima (Journal of Legal Studies and Researches, 2022)
International trade arbitration has moved from an exceptional system critical of its competition for justice provided by national courts in the state to a system complementary to this justice in cases where the latter is unable to provide speedy and specialized justice to international trade dealers, as these clients prefer it to the national judiciary. This arbitration was thus one of the most important pillars of the resolution of international trade disputes brought by the World Trade Organization in accordance with a special specificity that embodies WTO objectives.